Reflexivity, methodology and contexts in participatory digital media research: making games with Latin American youth in London - Paula, Bruno de (Learning, Media and Technology, 2021)
In this paper, I intend to explore the role played by reflexivity in grounding a more critical perspective when designing, implementing and analysing participatory digital media research. To carry out this methodological reflection, I will present and discuss a recently concluded research project on young people’s game-making in an after-school programme targeting Latin American migrants in London/UK. I will pay special attention to how my subjectivities influenced planning, data generation and analysis of this programme, and to how context, lived experiences, curricular decisions and interpersonal relationships shaped the kinds of knowledge produced through this research. Findings emerging from this experience included relevant dissonances between curricular design/decisions and the use of participatory approaches in game-making, and the limitations of traditional analytical categories within the Social Sciences field (e.g., gender and intersectionality) to understanding subjectivities expressed through game-making. This study offers relevant insights into the place of reflexivity in research on digital media production by young people by highlighting its complexity and by calling for more critical and less homogenising approaches to this type of research.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Artistes femmes, queer et autochtones face à leur(s) image(s): pour une histoire intersectionnelle et décoloniale des arts contemporains autochtones aux Etats-Unis et au Canada (1969-2019) - Journée, Aurélie (École des hautes études en sciences sociales, 2020)
Fin des années 1960 aux Etats-Unis, les Indians of All Tribes impulsent un mouvement de contestations sociales qui a pour but la reconnaissance des droits inhérents aux peuples autochtones à la souveraineté et à l'auto-détermination. L'American Indian Movement et sa branche féminine Women of All Red Nations s'emparent de ces questions sociales, politiques et culturelles. Femmes et hommes entament de concert un processus d'émancipation dont l'accomplissement ne cesse d'être repoussé par les politiques assimilatrices successives du gouvernement états-unien. Au Canada aussi, des mobilisations collectives éclatent dans les années 1980 et 1990, et culminent avec les événements de Restigouche (1984) et la Crise d'Oka (1990). Ces évènements majeurs inspirent toute une jeune génération d'artistes autochtones et de femmes en particulier, formées notamment à l'Institute of American Indian Arts à Santa Fe (Nouveau-Mexique). De formations universitaires approfondies, elles développent des démarches artistiques transdisciplinaires à mi-chemin entre l'histoire de l'art et l'ethnographie. Elles mettent en évidence la porosité et la friabilité des frontières instaurées dans tous les secteurs par la société dominante contre les groupes considérés comme minoritaires. A cette fin, le photographique - par lequel nous désignons la pratique, la technique et l'image photographiques - devient un outil stratégique majeur de réappropriation et de réaffirmation de ce qu'elles sont et tendent à incarner. Ces artistes femmes interrogent grâce à ce médium les façons dont elles ont été représentées et se représentent elles-mêmes dans le cadre de démarches critiques des stéréotypes dont elles font l'objet depuis plusieurs siècles d'appropriation culturelle. Elles repensent par ce biais leurs identités, les rapports qu'elles entretiennent à leurs corps, à leurs sexualités et à leurs genres, à l'aune de leurs propres spiritualités. Grâce à leurs images artistiques et politiques, fruits de pratiques fondées sur une analogie entre la violation de leurs droits, l'exploitation de leurs terres et territoires, et les violences sexuelles dont elles font l'objet, elles continuent à prendre part aux mouvements de résistance actuels qui s'opposent aux projets extractivistes face auxquels elles s'affirment, une nouvelle fois, en première ligne. A partir d'un corpus iconographique de près de 400 œuvres réalisées entre 1969 et 2019, et d'entretiens individuels avec des artistes et des militantes femmes et queer autochtones des Etats-Unis et du Canada, cette thèse a pour objectif de montrer en quoi ces images - en particulier photographiques configurent des épistémologies nouvelles dans une perspective intersectionnelle, décoloniale et anticapitaliste, et s'inscrivent dans la continuité d'un processus de réaffirmation des droits inhérents des peuples autochtones, garantis par la Déclaration des Nations Unies sur les Droits des Peuples Autochtones (2007)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Crash Override: How Gamergate (Nearly) Destroyed My Life, and How We Can Win the Fight Against Online Hate - Quinn, Zoë (PublicAffairs, 2017)
You've heard the stories about the dark side of the internet -- hackers, #gamergate, anonymous mobs attacking an unlucky victim, and revenge porn -- but they remain just that: stories. Surely these things would never happen to you. Zoe Quinn used to feel the same way. She is a video game developer whose ex-boyfriend published a crazed blog post cobbled together from private information, half-truths, and outright fictions, along with a rallying cry to the online hordes to go after her. They answered in the form of a so-called movement known as #gamergate--they hacked her accounts; stole nude photos of her; harassed her family, friends, and colleagues; and threatened to rape and murder her. But instead of shrinking into silence as the online mobs wanted her to, she raised her voice and spoke out against this vicious online culture and for making the internet a safer place for everyone. In the years since #gamergate, Quinn has helped thousands of people with her advocacy and online-abuse crisis resource Crash Override Network. From locking down victims' personal accounts to working with tech companies and lawmakers to inform policy, she has firsthand knowledge about every angle of online abuse, what powerful institutions are (and aren't) doing about it, and how we can protect our digital spaces and selves.Crash Override offers an up-close look inside the controversy, threats, and social and cultural battles that started in the far corners of the internet and have since permeated our online lives. Through her story -- as target and as activist -- Quinn provides a human look at the ways the internet impacts our lives and culture, along with practical advice for keeping yourself and others safe online.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Arte contemporáneo, violencia y creación feminista. "Lo personal es político" y la transformación del arte contemporáneo - Collado, Ana Martínez (Dossiers feministes, 2014)
Este texto analiza la transcendencia de la revolución feminista que se inició en los años 60 a partir del lema «Lo personal es político» y su influencia en la transformación del arte contemporáneo. En este contexto el trabajo desarrollado por las prácticas artísticas y la crítica feminista en relación a la denuncia de la violencia contra la mujer ocupa una posición destacada. A lo largo de estas últimas décadas no sólo ha evidenciado la violencia como un hecho continuado y global hacia la mujer sino que, además, ha iniciado nuevas narraciones que dan respuesta a un drama considerado socialmente como un irremediable «trágico final».
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Género y postcolonialismo en la creación videográfica: mujeres que escriben con la cámara y seducen en la pantalla - López, Xesqui Castañer (Dossiers feministes, 2014)
Postcolonialismo y feminismo utilizan conceptos comunes para el análisis y de/construcción de las narrativas dominantes. En países donde la colonización ha hecho estragos, las mujeres ponen en valor su empoderamiento como protagonistas de su destino. En esta línea las mujeres han aportado sus propuestas feministas para una nueva visión de lo colonial/postcolonial. Este trabajo pretende hacer un chequeo por aquellos trabajos videográficos de mujeres que, después de haber sido colonizadas, han realizado una descolonización cultural, situando su creatividad en varios continentes.
Keywords: 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _À vérifier-Cinéma